The Great Recession in the US from the Perspective of the World Economy. (1st July 2016) - ,
Abstract : In this article, the economic crisis from the US perspective is analyzed, using a Marxist approach. As the so-called Great Recession constitutes a general crisis of the capitalist economy at world level, this article intends to provide an analytical framework to explain it from the profitability of capital point of view, while emphasizing the meaning of the real estate bubble and the placement of the US economy in the world system. In doing so, an additional objective of this article is to provide elements to reveal the limitations of the conceptions of the theory of the crisis based on income distribution, finance, neoliberalism, and generally any aspect outside the core of the process of capitalist valorization as the key explaining factor.